Nanotechnology in diagnosis, treatment and prophylaxis of infectious diseases - Rai, Mahendra; Kon, Kateryna Volodymyrivna (Academic Press is an imprint of Elsevier, 2015)
Nanotechnology in Diagnosis, Treatment and Prophylaxis of Infectious Diseases delivers comprehensive coverage of the application of nanotechnology to pressing problems in infectious disease. This text equips readers with cutting-edge knowledge of promising developments and future prospects in nanotechnology, paying special attention to microbes that are now resistant to conventional antibiotics, a concerning problem in modern medicine. Readers will find a thorough discussion of this new approach to infectious disease treatment, including the reasons nanotechnology presents a promising avenue for the diagnosis, treatment, and prophylaxis of infectious diseases. Provides a comprehensive overview of the use of nanotechnology in the treatment and diagnosis of infectious diseasesCovers all common types of infective agents, including bacteria, viruses, fungi, and protozoa, along with their vectors, ticks, mosquitoes, flies, etc. Delivers commentary from an international researcher base, providing insights across differing economic statusesIncludes a foundation of basic nanotechnological concepts to aid in designing new strategies to combat several pathogenic diseases and cancerIllustrates the high antimicrobial potential of nanoparticles, ultimately demonstrating how they are a promising alternative class that can be successfully used in fighting a myriad of infections.